191k views
4 votes
Drag expressions to complete each equation.

Drag expressions to complete each equation.-example-1
User BertNase
by
5.7k points

1 Answer

3 votes


a^(-b) =(1)/(a^(b))


(a^(b))/(a^(c)) = a^(b-c)


(a^(c))/(b^(c)) =((a)/(b) )^(c)


When you have a negative exponent, you move the variable with the negative exponent to the opposite side of the fraction to make the exponent positive.

For example:


x^(-2) =(1)/(x^(2))


(1)/(x^(-2)) =(x^(2))/(1) or
x^(2)


When you have an exponent divided by an exponent, you subtract the exponents together.

For example:


(x^5)/(x^2) =x^(5-2) =x^3


(x^2)/(x^1) = x^(2-1) = x^1


When you multiply an exponent directly into a variable with an exponent, you multiply the exponents together.

For example:


(x^(2) )^(4) = x^8


((x^2)/(y^3) )^5=(x^(10))/(y^(15))


((x^1)/(y^1) )^b = (x^b)/(y^b)

User Bentley Carr
by
6.1k points